Association of COVID-19 Vaccine Intake with Diagnosis, Hospitalization, and Oxygenation/Ventilation: A Longitudinal Analysis, 2021–2022, Japan - Satomi Odani; Hitoshi Honda; Takahiro Tabuchi (Vaccines)
Background/Objectives: Japan’s COVID-19 vaccination campaign achieved high coverage by 2022, yet limited national-level data has hindered evaluations of vaccine effectiveness. This study analyzed the impact of vaccines on infection outcomes while considering socioeconomic and behavioral factors in the Japanese population. Methods: A total of 19,482 individuals aged 16–81 years, who participated in both the 2021 (baseline) and 2022 (follow-up) waves of an Internet-based survey, were analyzed. Vaccine intake during the follow-up period (0/1/2+ doses) served as the exposure, while outcomes included COVID-19 diagnosis, hospitalization, and receipt of oxygenation/ventilation. Adjusted prevalence ratios (APRs) were calculated using Poisson regression models, controlling for baseline characteristics such as vaccination status, infection history, underlying medical conditions, socioeconomic factors, and preventive behaviors. Results: Overall, 81.6% of respondents received at least 1 dose of COVID-19 vaccine during the follow-up period. Among those without COVID-19 history at baseline (N = 19,182), 10.9% were diagnosed with COVID-19 in the past year, and 6.6% in the past 2 months. Respondents who received 1 or 2+ doses had lower diagnosis rates (APR = 0.76 and 0.43, respectively). For the past 2 months, only those with 2+ doses showed a significant reduction (APR = 0.51). Among 1999 diagnosed cases, those with 1 or 2+ doses showed lower hospitalization and oxygenation/ventilation likelihoods, though these differences were not statistically significant. Conclusions: The results supported the protective effect of COVID-19 vaccines against infection. Continued research is essential to further clarify the complex influence of vaccination, individual characteristics, and preventive behaviors on COVID-19 morbidity at the population level.